2014
DOI: 10.1589/jpts.26.899
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Underwater Gait Training on Balance Ability of Stroke Patients

Abstract: [Purpose] The purpose of this study was to investigate the effects of underwater treadmill gait training on the balance ability of stroke patients. [Subjects] Twenty-two patients with stroke were randomly assigned to an underwater treadmill group (n =11) or a control group (n =11). [Methods] Both groups received general rehabilitation for 30 min per session, 5 times per week, over a 4-week period. The underwater treadmill group received additional underwater gait training for 30 min per session, 5 times per we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 28 publications
0
30
2
2
Order By: Relevance
“…27 Researchers also evaluate the effects of underwater treadmill training and concluded that compared with the general rehabilitation programme, underwater treadmill gait training was not more effective at improving the balance ability of stroke patients than land-based training. 28 Compared with the studies described above, we observed some differences depending on the degree of stroke severity, the length of time since stroke onset and the specific exercise training protocol. We also concluded that underwater treadmill training resulted in gait improvement and that the Halliwick and Ai Chi methods, in addition to obstacle training, may benefit both dynamic and static balance.…”
Section: Discussioncontrasting
confidence: 59%
“…27 Researchers also evaluate the effects of underwater treadmill training and concluded that compared with the general rehabilitation programme, underwater treadmill gait training was not more effective at improving the balance ability of stroke patients than land-based training. 28 Compared with the studies described above, we observed some differences depending on the degree of stroke severity, the length of time since stroke onset and the specific exercise training protocol. We also concluded that underwater treadmill training resulted in gait improvement and that the Halliwick and Ai Chi methods, in addition to obstacle training, may benefit both dynamic and static balance.…”
Section: Discussioncontrasting
confidence: 59%
“…To our knowledge, there have been only two reports on effectiveness of ATT on gait ability in stroke patients. Park et al [ 24 ] reported improvement in balance ability before and after ATT in stroke patients. Jung et al [ 23 ] reported that the addition of weight on the affected leg reduced unwanted flotation in chronic stroke patients during ATT, leading to increased stance stability.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this training is popular as a training method for elder persons and persons in rehabilitation, etc. [39,40]. The conventional assistive devices, which contain many electrical parts, will be difficult to apply for the underwater training from the waterproof point of view.…”
mentioning
confidence: 99%